Pengaruh Penanaman Spiritual Quotient (SQ) Terhadap Pembentukan Karakter Peserta Didik Melalui Pembelajaran Pai Di Sd Inp. 5/81 Mallari Kecamatan Awangpone - Nurmiati, Nurmiati; L, Idrus (JURNAL AL-QAYYIMAH, 2020)
The use of methods and techniques of instilling Spiritual Quotient (SQ) in the teaching of Islamic education at SD Inpres 5/81 Mallari, Awangpone District, is always directed towards the students' spiritual experiences. The effects of instilling SQ on students' character building through the teaching of Islamic education at SD Inpres 5/81 Mallari, Awangpone Subdistrict are: 1) Partially: spiritual-religious variable does not have significant influence on character building but it has a positive and strong correlation; socio-religious relation variable has no significant effect on character formation, but have a positive and strong correlation; social ethics variable has a significant influence on character formation and have a positive and very strong correlation. 2) Simultaneously, spiritual-religious variables, socio-religious relations, and social ethics have significant influence in building of learners’ character and have a very strong correlation to the formation of learners' characters.